1990
DOI: 10.1136/bjo.74.4.242
|View full text |Cite
|
Sign up to set email alerts
|

Orbital haemorrhage induced by labour.

Abstract: A case of acute orbital haemorrhage induced by labour is reported in a woman giving birth for the eighth time. The diagnosis was confirmed by computed tomography. The haemorrhage subsided spontaneously within three weeks. The mechanism of orbital haemorrhage following certain kinds of strain is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…Some venous ab normalities such as venous varix may be sus pected because intermittent exophthalmos was not fully excluded in these cases. Some Replacing vicariously the menses [7] Appearing at the climacteric [7] Toxic agents [7] authors have suggested the existence of ve nous anomalies in this disease [1,3,6]. In our cases, the symptoms of acute orbital pain, vomiting, proptosis with limitation of motility and ecchymosis of the eyelid oc curred.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Some venous ab normalities such as venous varix may be sus pected because intermittent exophthalmos was not fully excluded in these cases. Some Replacing vicariously the menses [7] Appearing at the climacteric [7] Toxic agents [7] authors have suggested the existence of ve nous anomalies in this disease [1,3,6]. In our cases, the symptoms of acute orbital pain, vomiting, proptosis with limitation of motility and ecchymosis of the eyelid oc curred.…”
Section: Discussionmentioning
confidence: 69%
“…They include vascular disor ders [1,[7][8][9], blood disorders [1,[10][11][12][13][14][15] and other generalized or local causes [1,2,4,6,7,16,17]. Case 1 was accompanied with vascular abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also be caused by nontraumatic activity such as manual labour (Geyer et al, 1990), scuba diving (Chen and Kucharczyk, 1988), sinusitis (Leopold et al, 1980;Zalzal, 1991), weight lifting (Katz and Carmody, 1985), as blood coagulopathies (Guirgis et al, 2002) and venous malformations (Krohel and Wright, 1979). All these lead to blood vessel (usually venous) rupture and entrapping of the blood clot between the periosteum and underlying orbital bone.…”
Section: Discussionmentioning
confidence: 98%
“…There are also other reported causes of SOH, which all result in increased pressure of orbital veins. These include manual labour (Geyer et al, 1990), scuba diving (Chen and Kucharczyk, 1988), sinusitis (Leopold et al, 1980;Zalzal, 1991), weight lifting (Katz and Carmody, 1985), as blood coagulopathies (Guirgis et al, 2002) and venous malformations (Krohel and Wright, 1979) The diagnosis of traumatic SOH is easy to establish with computed tomography (CT) and magnetic resonance imaging (MRI), but in nontraumatic cases other pathologies should be considered (Lieger et al, 2007;Wanyura et al, 2007). In most instances SOH does not require urgent surgery.…”
Section: Introductionmentioning
confidence: 99%